Financial Integration and International Risk Diversification - Amiri, Kaouther; Talbi, Besma (The Economics and Finance Letters, 2014)
The effect of international financial integration on performance strategies diversification is ambiguous for countries émergents1. It is explained by two reasons: hand, financial integration of national markets makes international diversification portfolios more efficiently, and helping the transition from one market to another and increasing efficiency of financial markets. On the other hand, financial integration increased correlations between national financial markets, reducing income strategies international diversification. We will show that this ambiguity is due to the use different properties with different testing procedures provided in the literature econometric. This is of particular interest to the present unit root test in the presence arch.